THE EMPOWERMENT OF COASTAL COMMUNITY THROUGH SHARIA TOURISM MANAGEMENT: A CASE STUDY OF SANTEN ISLAND BANYUWANGI REGENCY - M. Khoirul Hadi Asy’ari Miftahul Ulum (LEMBAGA PENELITIAN, PENGABDIAN PADA MASYARAKAT, PENINGKATAN AKTIVITAS INSTRUKSIONAL, PENINGKATAN DAN PENJAMINAN MUTU UNIVERSITAS ISLAM MAJAPAHIT, 2020)
Tourism has profound implications for global economic development. The expected tourism development is one which appreciates the local culture and upholds the Islamic values. Poverty as the common problem of coastal community makes empowerment as an important aspect to achieve better standard of living. Coastal community can establish the tourism sectors in the context of ecotourism. Ecotourism is a tourism development that is adapted to the conditions and potential of the local area. Thus, Sharia tourism is a reflection of the anxiety of government and society in realizing the concept of tourism development that has impact on the economic development of the community. There are many economic benefits derived from ecotourism such as can advance the economy sector and the economic values of the environment. Ecotourism promotes the economy of the community through empowerment and enhances the employment for coastal communities or local residents, so that can create the self-reliance and increase the income. Therefore, this research is conducted with the aim is to explore how the empowerment and the impact of economic sector for the coastal communities through newly implemented management by the government, that is Sharia management. This management is still relatively new in Santen Island of Banyuwangi regency, which is a tourism asset for local residents. This research is qualitative descriptive, using analytical descriptive.